If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -6(x + 8) = 60 Reorder the terms: -3x + -6(8 + x) = 60 -3x + (8 * -6 + x * -6) = 60 -3x + (-48 + -6x) = 60 Reorder the terms: -48 + -3x + -6x = 60 Combine like terms: -3x + -6x = -9x -48 + -9x = 60 Solving -48 + -9x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -9x = 60 + 48 Combine like terms: -48 + 48 = 0 0 + -9x = 60 + 48 -9x = 60 + 48 Combine like terms: 60 + 48 = 108 -9x = 108 Divide each side by '-9'. x = -12 Simplifying x = -12
| -3pq+spr-7p-6=-6q-5 | | 2a+(a+87)=180 | | .3333x=9 | | -7x-2(-7x+2)=38 | | 5d-d-2d+3d=0 | | x^2-15x+82=0 | | -2x+-3x=15 | | 2(r-3)=4(-3r-5) | | 7xy+0=7xy | | 2x^3-6x^2+6x-10=0 | | 17d-16d=14 | | 6(6)-33=d | | 3x^3-5x^2=0 | | 180-x-10=5(90-x) | | 180-x-10=3(90-x) | | 6a-12=30 | | 10x^2-x-42=0 | | 13x+13=11x+15 | | 2(x-7)+5x=153 | | 12x-23=49 | | 13y-3=23 | | 8x^3-64r^2+r-8=0 | | 14x+2=2+14x | | 2.6v=-28.6 | | 6(3)+1=c | | x+5=6x+49 | | 15r-7r=8 | | (8+x)x(10+x)=180 | | 3a^2+7a-20=0 | | t+9t=20 | | -(-6.9)=42.8 | | ab*3a=1564 |